Reciprocal Influence of Obesity and Vitamin D Deficiency in Covid-19 Survivors (Eurasian Journal of Research, Development and Innovation, 2024)
Worldwide, the prevalence of obesity has increased dramatically during the last four decades. Recent years vitamin D deficiency has also been scrutinizing as a cause of obesity. There is growing evidence that vitamin D has a significant role in metabolism, in particular in regulating the glucose homeostasis. Furthermore, a number of studies have suggested obesity as an independent risk factor of COVID-19 severity. After COVID19 pandemic, it is topical to assess the link between obesity and vitamin D deficiency especially in people who suffered from SARS-CoV-2 infection before. Aim: To assess vitamin D levels in people with and without obesity on those who underwent COVID-19 prior to the study. To study the mutual influence of obesity and vitamin D deficiency in these patients. To identify is there any link between severity of COVID-19 and obesity.